Knowledge about Fertile Period and its Determinants among Reproductive Aged Women in Bangladesh - Khatun, Sathi; Hasan, Md. Mehedi; Haque, Md. Aminul (Insights in Public Health Journal, 2024)
Abstract Background: The older population in Bangladesh is growing rapidly, from 8.0% in 2020 to 22.0% in 2050. However, the determinants of active aging are scarcely known. Objective: The study aimed to assess the determinants influencing the active aging situation in Bangladesh. Methods: A cross-sectional study was conducted among 518 older adults aged 60 years and over. Following the WHO active aging model, the respondents’ socio-demographic, personal, behavioral, and physical environment and health and social services characteristics were collected using a semi-structured questionnaire. Multiple linear regression was performed to determine the determinants, followed by the bivariate level of analysis. Results: The determinants of active aging were deeply rooted in the respondents' socio-cultural, economic, and spatial conditions. Nine out of 23 determinants, like marital status, income, decision-making capacity, regular walking/physical exercise, smokeless tobacco consumption, newspaper reading as a leisure activity, use of medicine, and health service accessibility, significantly influence active aging. The active aging score was 10-15% higher among the respondents who regularly adhered to the above determinants. Conclusion: Effective initiatives are needed to improve the socio-cultural, economic, and health system-related determinants of active aging to enhance the active aging situation. Concerned bodies of the country, ministries, departments, and development partners should take appropriate measures to increase awareness and the participation of people in lifestyle-related determinants to improve the active aging situation in the country.